Research on the Optimization of Public Management System in the Construction of Smart Cities - Wu, Bin (SHS web of conferences, 2025)
This article delves into the intricacies of refining public management systems to bolster the development of smart cities, aiming to enhance governance efficiency, elevate public service standards, and enrich the overall quality of life for residents. It offers a thorough examination of the existing landscape and primary hurdles in public management within the context of smart city initiatives, pinpointing gaps in resource integration, policy flexibility, and technological deployment. By considering the interplay of technology, resources, and policy, the article outlines a holistic optimization framework. It champions the strategic adoption of cutting-edge technologies like big data, artificial intelligence, the Internet of Things, and cloud computing to craft a forward-thinking, citizen-centric public management system. This framework prioritizes data-driven decision-making, fosters more scientific and timely resource allocation, and underscores the importance of improving residents’ experiences in the digital age. The proposed optimization strategy not only lays a theoretical foundation for the sustainable evolution of smart cities but also serves as a practical blueprint for future endeavors, steering smart city management toward greater intelligence, precision, and service orientation.